Children Well-Being dalam Perspektif “Invisible Needs”: Mengungkap Kebutuhan Tak Terlihat pada Anak Usia Dini - Azka Putri Ayuning Tyas Aziz; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study explores invisible needs in early childhood within the context of children’s well-being, showing that parenting often focuses more on physical and academic needs than emotional ones. Using a qualitative approach through parent interviews, the findings reveal that children need emotional security, consistent attention, and opportunities to express their feelings to support better emotional regulation and social interaction. Unmet needs may appear as irritability, withdrawal, and social difficulties. Overall, the study emphasizes that children’s well-being should be understood not only from physical aspects but also from emotional and relational dimensions, so parents need to be more aware of needs that are not always visible